(NmAJSTRI P(B'(NQTI L)QÆNÆJ (B:s)E (NOPOW)QÆDANNQ (B/s)E - (NdUBECXKIJ(B, (NkAROLX(B,s; (NlUCKEWI^(B, (NbORIS(B,s; (NlUCKEWI^(B, (NwASILX(B,s; (NkOPT)QÆLOW(B, æ(NGOR(B,s)E ((NkI)QÇW (B:s)E (NwESELKA(B,s, 1973)
(NzB)QÆRKA HUDOVNÆH OPOWÆDANX PRO KOMPOZITORÆW sWÆTU(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (N~AJKOWSXKIJ p(B. )Qæ.s)E; (NgAJDN f(B. (Nj(B.s; (NmOCART w(B. (Na(B.s; (NbETHOWEN l(B.s; (NpAGAN)QÆNÆ n(B.s)E; (N{OPEN f(B. (Nf(B.s; (Nl)QÆST f(B.s)E; )Qæ(NSTORÆQ MUZIKIs)E -- (NkOMPOZITORIs; (NMUZIKANTIs; (NKOMPOZITORIs; (NROZPOW)QÆDÆs)E; (NTWOR^)QÆSTXs)E